Physiological dimension of altitude training in raising the vital ability. - zaoui, ali; medjaralou, ahlem (sports creativity, 2025)
The aim of the study was to address the urgent issues of physiological adaptation in order to increase the lifting of the vital capacity of both the circulatory system and the respiratory system, our choice of this topic was to enrich and benefit the athlete, his staff, and researchers, especially judo athletes, in helping them provide various interpretations of these phenomena. Where it was divided into two axes, the axis of Afol was aimed at knowing the extent of increasing the efficiency of the respiratory system for athletes during their stays, training at the high level, and the low return to conducting competitions at sea level. As for the second axis in raising the efficiency of the circulatory system, the sample of the study was randomly selected from 19 wrestlers of the national judo team, it was a middle class and the elderly people ranged between 19 and 30 years old, and they used the experimental method. We used a set of experimental tests, including a 5-minute test for Brikci et Dekkar to verify the first axis